PEGylation of genistein-loaded bovine serum albumin nanoparticles and its effect on in vitro cell viability and genotoxicity properties - Ferrado, Joana Belén (2023)
Self-assembled bovine serum albumin nanoparticles loaded with the isoflavone genistein have shown apoptosis-mediated cytotoxicity against murine mammary adenocarcinoma F3II cells. Due to their protein nature and small particle size (13–15 nm), their parenteral administration could be affected by possible immunogenic reactions and rapid clearance from the bloodstream. To avoid these problems, PEGylation of the systems was achieved in this work by using a 30 kDa methoxy-polyethylene glycol carbonyl imidazole derivative through the reaction between the carbonyl imidazole group and the amino groups of Lys residues on the protein surface, which was confirmed by a 17% reduction in the available amino groups content measured by the o-phthaldialdehyde method. PEGylated isoforms were obtained, showing an increase of particle size from 13 to 15 nm to around 260 nm, and were purified by SEC-FPLC and characterized by SDS-PAGE, DLS and AFM techniques. The effect of PEGylation on BSAnp-Gen cytotoxicity and genotoxicity against F3II cells was evaluated in vitro by MTT assay, flow cytometry analysis and micronucleus assay. From the results, PEGylation produced an improvement of the biological properties of genistein-loaded nanoparticles in terms of cytotoxicity (lower IC50), not affecting the induction of apoptosis, decreasing the genotoxicity of the systems (less induction of micronucleus formation).